2002
DOI: 10.1179/000349802125000826
|View full text |Cite
|
Sign up to set email alerts
|

Onchocerciasis: the clinical and epidemiological burden of skin disease in Africa

Abstract: An attempt was made to assess the true public-health importance of onchocercal skin disease throughout the African region and hence provide an objective basis for the rational planning of onchocerciasis control in the area. The seven collaborative centres that participated in the study (three in Nigeria and one each in Ghana, Cameroon, Tanzania and Uganda) were all in areas of rainforest or savannah-forest mosaic where onchocercal blindness is not common. A cross-sectional dermatological survey was undertaken … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(79 citation statements)
references
References 21 publications
4
73
1
1
Order By: Relevance
“…A large multi-country study has shown that OSD entails a grave burden and that its symptoms have significant personal and psycho-social effects, not only on the affected individuals but also on their families and communities (Murdoch et al 2002). Of the clinical spectra of onchocerciasis, pruritus was the most frequently observed symptom among the study subjects, which is often very serious and the main cause of sleeplessness, fatigue and weakness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large multi-country study has shown that OSD entails a grave burden and that its symptoms have significant personal and psycho-social effects, not only on the affected individuals but also on their families and communities (Murdoch et al 2002). Of the clinical spectra of onchocerciasis, pruritus was the most frequently observed symptom among the study subjects, which is often very serious and the main cause of sleeplessness, fatigue and weakness.…”
Section: Discussionmentioning
confidence: 99%
“…While the disastrous effects of ocular damage by river blindness have always been high priority as a public health problem, skin disease has received scant attention. Nonetheless, large multi-country studies have recently shown that onchocercal skin disease (OSD) entails a grave burden and that its symptoms have significant personal and psycho-social effects, not only on the affected individuals but also on their families and communities (Murdoch et al 2002). In Ethiopia, eye lesions and blindness due to the disease appear to be absent or uncommon (WHO 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Onchocerciasis is currently endemic in 30 African countries, Yemen, and isolated regions of South America. A study to assess the true public-health importance of onchocercal skin disease throughout the African region was conducted in 7 centers (3 in Nigeria and 1 each in Ghana, Cameroon, Tanzania and Uganda) and involved 5459 subjects (69). A strong correlation was found between the prevalence of itching, which affects 42% of the population aged 20 years, and the level of endemicity, which was measured by the prevalence of onchocercal skin lesions.…”
Section: Helminthic Infectionsmentioning
confidence: 99%
“…In each selected village a sample of adults is examined for the presence of palpable subcutaneous onchocercal nodules and the prevalence of nodules is calculated. Previous studies had shown that the severity of onchocercal disease in the community, and thus its public health importance, is related to the level of onchocerciasis endemicity as also reflected in the prevalence of nodules [2,66,67]. Based on available data on this relationship, an expert committee recommended in the early 1990s that, in order to control onchocerciasis as a public health problem, ivermectin treatment should be provided to all high risk communities where the prevalence of onchocercal nodules in adults was greater than 20% [68].…”
Section: Introductionmentioning
confidence: 99%